CEMARAN Staphylococcus aureus DAN Pseudomonas aerogenosa PADA STETESKOP DIRUMAH SAKIT - lutpiatina, leka (POLTEKKES KEMENKES YOGYAKARTA, 2017)
Medical devices that are susceptible to bacteria contaminated one of them is a stethoscope. Nosocomial infections that are problematic in the hospital include Staphylococcus aureus and Pseudomonas aerogenosa. These bacteria can cause mild skin infections to serious life-threatening infections. The purpose of this research is to know the existence of bacteria contamination of Staphylococcus aureus and Pseudomonas aerogenosa on steteskop at Banjarbaru hospital. This research uses descriptive survey method, which is a research method to describe objectively based on facts found. The samples were stethoscope in child care room, internal medicine room, delivery room, post partum room, perinatology room, and post-surgical treatment room at Banjarbaru hospital for 30 stethoscopes.The result of the research was found contamination of Staphylococcus aureus and Pseudomonas aerogenosa on steteskop. The site home condition of the research data was 66.7% cleaned daily, the storage method was placed on the table 70% and the duration of using the set home more than 1 year as much as 70%. The conclusion of stethoscope at Banjarbaru Hospital was contaminated with Staphylococcus aureus by 70% and Pseudomonas aerogenosa by 17%. The suggestion of research can be continued by knowing the existence of Staphylococcus aureus resistant antibiotic and Pseudomonas aerogenous antibiotic resistant at steteskop at Hospital.